Logistic Regression Analysis of Escherichia Coli Contaminants on the Tofu Water in Lowokwaru Market Malang City - Sari, Nia (Universitas STRADA Indonesia, 2018)
The purpose of this research know to the influence of Escherichia coli contaminants on the tofu water in lowokwaru market Malang city. The research method used analytical survey with cross sectional approach with simple random sampling and obtained 20 samples of traders.The result of the research showed that the food hygiene and sanitation the >90,2% sample of 10 (50%), the appearence and tofu the > 80% sample of 9 (45%), Up impurities Escherichia coli that sample of 0 per 100 ml sample as much 8 (40%). Based on the results ogistic regression presentation and processing Tofu to Escherichia coli with significance value = 0.099 > (Î±= 0.05) then H0 is accept. No effect the presentation of and Tofu processing against Escherichia coli who sold street vendors. And the result of statistical test hygiene and food sanitation against escherichia coli by using logistic regression with significans value = 0.032 < (Î±= 0.05) then H0 is reject so there an effect the Hygiene snd food sanitation escherichia coli sold street vendors and value of square as 0.434 means and the presentation of food hygiene and sanitation and processing Tofu affect escherichia coli as 43,4% Therefore, it is necessary to review the place of hygiene sanitation and presentation of tofu processing sold street vendors in the market lowokwaru. The water is very important bacteriology tofu for a measurement degree of pollution. Socialize and was conducted by means of maintaining healthy food hygiene and sanitation.